Contemporary Psychometrics (IntechOpen, 2026)
In an era marked by rapid social, cultural, and technological change, the field of psychometrics is evolving to meet new challenges and possibilities. Contemporary Psychometrics - New Developments and Applications offers a timely and rigorous exploration of emerging perspectives, methods, and applications in psychological assessment. This volume brings together international scholars whose contributions reflect the diversity and complexity of modern psychometric inquiry. From innovative theoretical frameworks to culturally sensitive approaches, the chapters address key questions facing researchers and practitioners today. Highlights include: • A comprehensive overview of contemporary psychometric models and their practical applications. • A critical look at psychometric network analysis as an alternative for understanding complex psychosocial systems. • The introduction of etno-psychometry, a powerful approach that balances psychometric rigor with cultural relevance. • Original research on new test development and validation, including studies in positive psychology in sports, engineering education, and child attention assessment. Whether you are a researcher, practitioner, or graduate student, this book will provide valuable insights into the current state and future directions of psychometric science. By showcasing methodological innovation and cross-cultural perspectives, it invites readers to rethink how we define, measure, and interpret human behavior in diverse contexts.